Human frontiers, environments, and disease : past patterns, uncertain futures - McMichael, A. J. (Anthony J.) (Cambridge University Press, 2001)
This compelling account charts the relentless trajectory of humankind across time and geography, and its changing survival patterns, from several million years ago when our ancient ancestors roamed the African Savannah to today's populous, industrialised, globalising world.
Keywords: World health.; Diseases and history.; Sustainable development.; Climatic changes -- Health aspects.; Human ecology.; Social medicine.; Ecology.; Social ecology.; Global Health; Social Medicine; Ecology; Social Environment; Santé mondiale.; Maladies et histoire.; Développement durable.; Climat -- Changements -- Aspect sanitaire.; Écologie humaine.; Médecine sociale.; Écologie.; Écologie sociale.; sustainable development.; human ecology.; ecology.; HEALTH & FITNESS -- Health Care Issues.; MEDICAL -- Public Health.; MEDICAL -- Health Policy.; HEALTH & FITNESS -- Diseases -- General.; MEDICAL -- Diseases.; MEDICAL -- Health Care Delivery.; Social medicine; Climatic changes -- Health aspects; Diseases and history; Human ecology; Sustainable development; World health; Climatic changes.